Challenges for Migration Governance: Theoretical Framework and Remarks on the Mexican Case - Fresneda Camacho, Edel J. (2025)
From a qualitative perspective, this work examines the notion of governance of migration and its implications on the reconfiguration of Mexican migration law. To this end, brief reflections are included to expand the theoretical framework of migration governance as an international construct, while considering the various obstacles that hinder its effective implementation across diverse contexts. These limitations are closely related to the inherent nature of human mobility and to the influence of prevailing political dynamics. Consequently, the analysis concludes that there exists an apparent contradiction between the persistence of a restrictive approach to migration management and the progress achieved in Mexican migration policy, as evidenced by recent reforms to the Migration Law and the Law on Refugees, Complementary Protection, and Political Asylum.